Self-enhanced PBAT and preparation method of film thereof
Self-reinforced PBAT particles were prepared by two-step method, combined with high mixer and twin-screw extruder technology, and the problem of poor processing performance of PBAT when improving mechanical properties was solved, achieving high mechanical properties and good processing performance of PBAT films, which are suitable for industrial production.
Patent Information
- Application Number
- CN202510383395.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
While improving the mechanical properties of existing PBAT plastics, their processing performance often deteriorates, resulting in increased difficulty in blowing films, limiting their application in industrial production.
Self-reinforced PBAT particles are prepared by a two-step method. First, conventional PBAT particles, crosslinking agents, lubricants, antioxidants and opening agents are premixed in a high mixer to form PBAT particles to be enhanced, and then blended with conventional PBAT particles in a twin-screw extruder to achieve dynamic crosslinking/branching of the dispersed phases through shearing to form a dispersed phase network to improve mechanical properties while maintaining continuous phases to ensure good processing performance.
It achieves the improvement of PBAT mechanical properties while maintaining its good processing performance, reducing the difficulty of blowing film, making PBAT film suitable for industrial production.
Smart Images

Figure CN119875329A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biodegradable plastics, and in particular to a method for preparing a self-reinforced PBAT and a film thereof. Background Art
[0002] Biodegradable plastics have attracted widespread attention as a substitute for traditional non-degradable plastics. PBAT (polybutylene terephthalate-adipate-butylene terephthalate) is a 100% biodegradable plastic that is widely used in the field of film packaging. However, compared with traditional plastics, PBAT has higher costs, lower modulus, and less than ideal mechanical properties. Generally speaking, chain extension can increase the molecular weight of PBAT and thus improve its film mechanical properties. For example, patent CN117417507A discloses a method for increasing the molecular weight of PBAT by chain extension. However, the higher the molecular weight of the polymer, the better the mechanical properties, and its processing performance usually deteriorates or even cannot be processed, which is not conducive to or even impossible to achieve industrial production.
[0003] Therefore, it is necessary to develop a method that can improve the mechanical properties of PBAT while maintaining its good processing performance, so as to reduce the difficulty of PBAT film blowing and make it more suitable for industrial production. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing self-reinforced PBAT particles suitable for industrial production, which improves the mechanical properties of PBAT while maintaining good processing performance.
[0005] The second object of the present invention is to provide a method for preparing a self-reinforced PBAT film suitable for industrial production, wherein the prepared PBAT film has good mechanical properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a self-enhanced PBAT, comprising the following steps:
[0008] (1) Premix conventional PBAT particles, crosslinking agent, lubricant, antioxidant, and anti-blocking agent in a high-speed mixer according to a certain mass ratio, and then extrude and granulate in a twin-screw extruder to obtain reinforced PBAT particles. The processing temperature range of the twin-screw extruder is 80 o C-145 o C, the mass percentages of the components of the PBAT to be enhanced are: PBAT 95.5-99.6%, cross-linking agent 0.2-3.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%; the cross-linking agent is ADR4468;
[0009] (2) The PBAT particles to be enhanced and the conventional PBAT particles are mixed and mixed in a twin-screw extruder to extrude and granulate to obtain self-enhanced PBAT particles, wherein the mass of the PBAT particles to be enhanced accounts for 10-40% of the total mass of the PBAT particles to be enhanced and the conventional PBAT particles; the processing temperature range of the twin-screw extruder is 80 o C-185 o C.
[0010] In step (1) of the present invention, the conventional PBAT particles are commercially available PBAT particles that have not been modified. The lubricant can be selected from one or more of PE wax, stearic acid, butyl stearate, stearic acid monoglyceride, and oleamide. The antioxidant can be selected from one or more of hindered phenol antioxidants and phosphite antioxidants. The anti-blocking agent can be selected from one or more of pentaerythritol stearate and calcined silica.
[0011] In step (1) of the present invention, the weight percentages of the components of the PBAT to be enhanced are preferably: PBAT 98.0-99.4%, cross-linking agent 0.25-1.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%; further preferably, the weight percentages of the components of the PBAT to be enhanced are: PBAT 98.5-99.0%, cross-linking agent 0.5-0.75%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%.
[0012] In step (1) of the present invention, the temperature of the high-speed mixer is from room temperature to 80 o C, the rotation speed is 200-1000 rpm, and the mixing time is 2-10 min.
[0013] In step (1) of the present invention, the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-145 o C, die temperature is 110-140 o C, the screw speed is controlled at 150-300 rpm.
[0014] In step (2) of the present invention, the mass of the PBAT particles to be enhanced accounts for 25-35% of the total mass of the PBAT particles to be enhanced and the conventional PBAT particles.
[0015] In step (2) of the present invention, the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-185o C, die temperature is 150-170 o C, the screw speed is controlled at 250-400 rpm.
[0016] The crosslinking agent ADR used in the present invention is also called a chain extender. Its molecular chain contains several reactive epoxy groups, which can be o C) reacts with the terminal carboxyl or even terminal hydroxyl groups of PBAT to form branching or even crosslinking. The present invention first prepares the PBAT particles to be reinforced by a high mixer and a twin-screw extruder. Since the epoxy group reaction activity of the crosslinking agent is not high at the extrusion temperature, it will only slightly react with the terminal carboxyl group of PBAT or not react. Then, the PBAT particles to be reinforced are melt-blended with more conventional PBAT particles in a twin-screw extruder. The conventional PBAT particles form a continuous phase, while the PBAT particles to be reinforced are easily sheared into a dispersed phase by the screw / barrel. At the same time, due to the high extrusion temperature, the PBAT particles to be reinforced react in situ with the crosslinking agent ADR4688 inside it to form a dispersed phase. At the same time, the ADR4688 located at the interface forms a co-crosslink at the dispersed phase / continuous phase interface, thereby obtaining a self-reinforced PBAT. The self-reinforced PBAT is a special multiphase system, and the physical properties of the matrix phase and the reinforcement phase are significantly different but the chemical structure is basically the same. In this way, in the conventional PBAT continuous phase, the cross-linked PBAT forms a dispersed phase network, which improves the overall strength of PBAT, while the continuous phase ensures overall thermoplasticity and better fluidity, making the processing process easier.
[0017] In a second aspect, the present invention provides a method for preparing a self-reinforced PBAT film, comprising the following steps:
[0018] (1) Premix conventional PBAT particles, crosslinking agent, lubricant, antioxidant, and anti-blocking agent in a high-speed mixer according to a certain mass ratio, and then extrude and granulate in a twin-screw extruder to obtain reinforced PBAT particles. The processing temperature range of the twin-screw extruder is 80 o C-145 o C, the mass percentages of the components of the PBAT to be enhanced are: PBAT 95.5-99.6%, cross-linking agent 0.2-3.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%; the cross-linking agent is ADR4468;
[0019] (2) The PBAT particles to be enhanced and the conventional PBAT particles are mixed and mixed in a twin-screw extruder to extrude and granulate to obtain self-enhanced PBAT particles, wherein the weight of the PBAT particles to be enhanced accounts for 10-40wt% of the total weight of the PBAT particles to be enhanced and the conventional PBAT particles; the processing temperature range of the twin-screw extruder is 80 o C-185 o C;
[0020] (3) The self-reinforced PBAT particles are blown into a film to obtain a self-reinforced PBAT film.
[0021] The preparation details of the above steps (1) and (2) are the same as those of the first aspect and will not be repeated here.
[0022] The film blowing in step (3) can be carried out according to conventional film blowing process. Preferably, the film blowing conditions are: the temperature of the first to fourth sections of the film blowing extruder is 140-170 o C, the blowing ratio (die diameter: film bubble diameter) is 1:2-3, and the film blowing stretch ratio is 1.2.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention adopts a two-step method to prepare self-reinforced PBAT, that is, the PBAT particles to be reinforced are first prepared at a relatively low temperature, and then the dispersed phase is dynamically crosslinked / branched / thickened by shearing at a relatively high temperature. The crosslinked / branched / thickened dispersed phase network improves the overall mechanical properties of PBAT, while the continuous phase ensures good processing (film blowing) performance of PBAT.
[0025] (2) The present invention adopts high mixing, granulation and film blowing, and has a simple process flow, is easy to operate, and is suitable for large-scale production.
[0026] (3) The PBAT film prepared by the present invention has good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments and comparison examples of the present invention, and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1The figure is a typical experimental process and mechanism diagram of preparing self-reinforced PBAT by the two-step method of the present invention, wherein the self-reinforced PBAT of the embodiment comprises a highly branched reinforcing phase and a continuous phase composed of conventional PBAT, and the two-phase structure of the self-reinforced PBAT ensures that it has good mechanical properties while also ensuring good processing properties;
[0029] Figure 2 The figure is a typical experimental process and mechanism diagram of preparing self-enhanced PBAT by uniform reaction method of the control example of the present invention, and the control example obtains uniformly enhanced PBAT;
[0030] Figure 3 The graphs of complex viscosity and storage modulus of PBAT samples prepared in some embodiments and comparative examples measured in a rotational rheometer as a function of angular frequency are shown;
[0031] Figure 4 The scanning electron microscope (SEM) microscopic morphology images of the extruded samples after brittle fracture in some embodiments and control examples and the atomic force microscope (AFM) modulus distribution image of the film surface in Example 3, wherein SEM images: (a) Control Example 4 (control sample without adding ADR), (b) Control Example 1, (c) Example 1, (d) Example 2, (e) Example 3; AFM phase image: (f) Example 3.
[0032] Figure 5 This is the reaction foaming diagram after extrusion using an extruder with a diameter of 48 mm for Control Example 2. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited thereto.
[0034] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0035] Conventional PBAT particles are TH801T coating grade PBAT from Xinjiang Lanshan Tunhe, with a melt flow rate MF of 6.0 g / 10min (190 o C, 2.16 kg), terminal carboxyl content <40 mol / ton.
[0036] Example 1
[0037] By mass percentage, the PBAT particles to be enhanced include 99.15% conventional PBAT particles, 0.25% cross-linking agent (ADR 4468), 0.1% lubricant (white oil), 0.1% antioxidant (bis (4-octylphenol) diphosphate), 0.2% antioxidant (tri (2,4-di-tert-butyl) phenyl phosphite), and 0.2% anti-blocking agent (pentaerythritol stearate).
[0038] Calculated by mass percentage, the self-reinforced PBAT particles include 70% conventional PBAT particles and 30% PBAT particles to be reinforced.
[0039] Preparation of PBAT particles to be enhanced: conventional PBAT particles, crosslinking agent (ADR-4468), lubricant (white oil), antioxidant (bis(4-octylphenol) diphosphate, tris(2,4-di-tert-butyl)phenyl phosphite), and blocking agent (pentaerythritol stearate) were weighed according to the formula, and all the raw materials were directly put into a 50 L high-speed mixer (SHR-50A, Zhangjiagang Plasman Machinery Manufacturing Co., Ltd.) at 40 o C, blending at 500 rpm for 2 min; then adding the mixture into a co-rotating parallel twin-screw extruder (φ36, L / D=36, Nanjing Keya Chemical Equipment Co., Ltd.) for mixing, plasticizing and extrusion, and pelletizing after stranding and air cooling to obtain the desired reinforced PBAT particles; the temperature of each section of the extruder is: the temperature of sections 1 to 10 is 80, 120, 130, 135, 140, 140, 145, 140, 145, 145 o C, die temperature is 140 o C; the speed is 240 rpm.
[0040] Preparation of self-reinforced PBAT particles and films: According to the formula, conventional PABT particles and PBAT particles to be reinforced were weighed and added into a co-rotating parallel twin-screw extruder (φ36, L / D=36, Nanjing Keya Chemical Equipment Co., Ltd.) for mixing, plasticization and extrusion, and then pelletized by stranding and air cooling to obtain self-reinforced PBAT particles; the temperature of each section of the extruder was: the temperature of sections 1 to 10 was 80, 135, 150, 160, 165, 175, 180, 185, 185, 170 o C, die temperature is 160 o C; the rotation speed is 350 rpm. The obtained self-reinforced PBAT particles were directly blown by a blown film extruder (SJ-50-850, Dalian Longyao Plastic Machinery Co., Ltd.) to obtain a PBAT film. The temperatures of the first to fourth sections of the blown film extruder are 150, 160, 170, and 150 °C, respectively, the blowing ratio (die diameter: film bubble diameter) is 1:3, and the blown film stretch ratio is 1.2.
[0041] The obtained PBAT film was subjected to a tensile property test according to GB / T1040.3-2006 to obtain tensile strength data.
[0042] The material melt index is tested using a standardized melt flow index tester. The specific method is: place the self-reinforced PBAT particle sample in the heating barrel of the tester, melt the material at a specified temperature at 190 ° C, and pass it through a standard mold with a load of 2.16 kg to measure the flow rate within 10 minutes. The flow rate is expressed as grams per 10 minutes (g / 10min). The self-reinforced PBAT particles are molded (160 o C, 5 min) into 1 mm thick discs and measured their o C, the viscosity and storage modulus in the range of 1-600 rad / s. The self-reinforced PBAT particle sample was placed in a mixing torque rheometer at 160 °C and mixed for 10 min, and the torque was obtained after equilibrium.
[0043] Example 2
[0044] The other steps are the same as in Example 1, but the amount of crosslinking agent in the PBAT particles to be reinforced is increased from 0.25% to 0.5%, and the amount of PBAT is reduced from 99.15% to 98.9%.
[0045] Example 3
[0046] The other steps are the same as those in Example 1, except that the amount of crosslinking agent in the PBAT particles to be reinforced is increased from 0.25% to 0.75%, and the amount of PBAT is reduced from 99.15% to 98.65%.
[0047] Example 4
[0048] The other steps are the same as those in Example 1, except that the amount of crosslinking agent in the PBAT particles to be reinforced is increased from 0.25% to 1.0%, and the amount of PBAT is reduced from 99.15% to 98.4%.
[0049] Example 5
[0050] The self-reinforced PBAT particles were expanded for production, and the extruder was replaced with HK-53 produced by Nanjing Keya Chemical Equipment Co., Ltd., with a screw diameter of 48 mm and an aspect ratio of 40: 1. Others were the same as in Example 2.
[0051] Comparative Example 1
[0052] Compared with Example 3, uniform reaction method extrusion granulation was carried out with the same raw material component content.
[0053] By mass percentage, the enhanced PBAT particles include 99.595% conventional PBAT particles, 0.225% cross-linking agent (ADR-4468), 0.03% lubricant (white oil), 0.03% antioxidant (bis(4-octylphenol) diphosphate), 0.06% antioxidant (tri(2,4-di-tert-butyl)phenyl phosphite), and 0.06% anti-blocking agent (pentaerythritol stearate).
[0054] Preparation of enhanced PBAT particles: According to the above formula, conventional PABT particles and crosslinking agent, lubricant white oil, antioxidant (bis(4-octylphenol) diphosphate), antioxidant (tri(2,4-di-tert-butyl)phenyl phosphite), and opening agent (pentaerythritol stearate) were weighed respectively, and all raw materials were directly put into a 5 L high-speed mixer (SHR-50A, Zhangjiagang Plasman Machinery Manufacturing Co., Ltd.) and stirred at 40 o C, blending at 500 rpm for 2 min; then the mixture was added to a parallel co-rotating twin-screw extruder (φ36, L / D=36, Nanjing Keya Chemical Equipment Co., Ltd.) for pre-mixing, and the desired pellets were obtained by strand air cooling and pelletizing; the temperatures of each section of the extruder were: 80, 120, 130, 135, 140, 140, 145 ... o C, die temperature is 140 o C; the speed is 240 rpm. Then the premix is sent to the extruder for mixing, so that ADR reacts evenly with PBAT. The temperature of each section of the extruder is: the temperature of the first to tenth sections is 80, 135, 150, 160, 165, 175, 180, 185, 185, 170 o C, die temperature is 160 o C; the speed is 350 rpm.
[0055] Preparation of reinforced PBAT film: The pellets were directly blown using a film blowing machine (SJ-50-850, Dalian Longyao Plastic Machinery Co., Ltd.) to obtain PBAT film. The temperatures of the first to fourth sections of the film blowing extruder were 150, 160, 170, and 150 °C, respectively, the blowing ratio (die diameter: film bubble diameter) was 1:3, and the film blowing stretch ratio was 1.2.
[0056] The performance testing method of the enhanced PBAT particles and films is the same as that of Example 1.
[0057] Comparative Example 2
[0058] A high starch content filled PBAT composite film was prepared with reference to CN 117603481A.
[0059] By mass percentage, 97.62% of thermoplastic starch TPS (TPS: brand A302, purchased from Shandong Shouguang Juneng Golden Corn Co., Ltd.), 0.2% of peroxide initiator (1,4-di-tert-butyl peroxyisopropylbenzene, half-life of 1 min at 182°C), 2% of crosslinking agent (triallyl isocyanurate), 0.03% of lubricant (white oil), 0.03% of antioxidant (bis(4-octylphenol) diphosphate), 0.06% of antioxidant (tris(2,4-di-tert-butyl)phenyl phosphite), and 0.06% of anti-blocking agent (pentaerythritol stearate) were mixed in proportion and put into a 50 L high-speed mixer (SHR-50A, Zhangjiagang Plasman Machinery Manufacturing Co., Ltd.) and stirred at 60 °C. o C, blending at 500 rpm for 10 min; then the mixture was added to a co-rotating parallel twin-screw extruder (φ36, L / D=36, Nanjing Keya Chemical Equipment Co., Ltd.) for mixing, plasticization, and extrusion, and pelletized by strand air cooling to obtain the desired pre-crosslinked TPS pellets; the temperatures of each section of the extruder were: 80, 85, 90, 100, 110, 120, 110, 100, 95, 90 o C, die temperature is 100 o C; the speed is 120 rpm. If the extruder with a diameter of 48 mm is used for extrusion in this step, under the same extrusion conditions, the shear force of the screw is strong, which causes the decomposition of peroxide, and the TPS surface has foamed, and it is impossible to produce continuous pre-crosslinked TPS strips ( Figure 5 ).
[0060] Pre-crosslinked TPS and conventional PBAT particles were added to a co-rotating parallel twin-screw extruder (φ36, L / D=36, Nanjing Keya Chemical Equipment Co., Ltd.) at a mass ratio of 3:7 for mixing, plasticization and extrusion, and then pelletized by strand air cooling to obtain PBAT / TPS composite particles; the temperatures of each section of the extruder were: 150, 155, 160, 160, 170, 180, 170, 160, 155, 150, respectively. o C, die temperature is 150 o C; the rotation speed is 120 rpm. The obtained pellets were directly blown by a blown film extruder (SJ-50-850, Dalian Longyao Plastic Machinery Co., Ltd.) to obtain a PBAT / TPS composite film. The temperatures of the first to fourth sections of the blown film extruder were 150, 160, 170, and 150 °C, respectively, the blow ratio (die diameter: film bubble diameter) was 1:3, and the blown film stretch ratio was 1.2.
[0061] The performance testing method of PBAT / TPS composite particles and composite films is the same as that of Example 1.
[0062] Comparative Example 3
[0063] Referring to CN 117603481A, peroxide was used to initiate cross-linking of PBAT, and a two-step method was used to prepare self-reinforced PBAT particles and films.
[0064] The rest is the same as the control example 2, the only difference is that the ratio of the PBAT particles to be enhanced is: conventional PBAT particles 97.2%, peroxide initiator (1,4-di-tert-butyl peroxyisopropylbenzene, half-life at 182°C is 1min) 0.2%, cross-linking agent (triallyl isocyanurate) 2%, lubricant (white oil) 0.1%, antioxidant (bis (4-octylphenol) diphosphate) 0.1%, antioxidant (tris (2,4-di-tert-butyl) phenyl phosphite) 0.2%, and anti-blocking agent (pentaerythritol stearate) 0.2%.
[0065] Comparative Example 4
[0066] The other steps were the same as in Example 1, but without adding the crosslinking agent ADR. The PBAT content in the reinforced PBAT particles was increased to 99.4%, and PBAT particles and films were obtained.
[0067] Table 1 below shows the performance data of PBAT films and particles prepared in various embodiments and comparative examples:
[0068] Table 1
[0069]
[0070] Tensile strength reflects the mechanical properties of PBAT film. Melt index can reflect the fluidity during processing, and the same is true for torque. Torque refers to the torsional moment required during processing. The greater the processing torque, the greater the resistance to the polymer material during processing, and the more difficult the processing. As can be seen from Table 1, the PBAT prepared in Control Example 4 has good processing properties, but the tensile strength needs to be improved. Although the introduction of TPS can reduce the cost of PBAT particles, the PBAT / TPS composite particles obtained in Control Example 2 have reduced mechanical properties and significantly reduced processing properties compared to Control Example 4. This is because the cross-linking network formed by the peroxide initiator and the cross-linking agent is denser and stronger than the branching reaction of ADR, which reduces the molecular chain mobility of PBAT, which is not conducive to processing and molding; and because the peroxide initiator is easy to decompose, it cannot be used in an extruder with a large screw diameter, making it unsuitable for large-scale industrial production. Comparative Example 3 refers to Comparative Example 2 and uses peroxide to initiate crosslinking of PBAT, and uses a two-step method to prepare self-reinforced PBAT particles. Compared with Comparative Example 4, the mechanical properties of PBAT are improved, but similar to Comparative Example 2, the melt index of the self-reinforced PBAT particles is greatly reduced, which is not conducive to processing and molding, and due to the use of peroxide initiators, there is also a problem that it is not suitable for large-scale industrial production. Comparative Example 1 uses a relatively mild ADR and uses a uniform reaction method to react with PBAT for enhancement. During the reaction, ADR is used as a chain extender, so the mechanical properties will be improved after addition, but the processing performance will also deteriorate. Adding too much chain extender will deteriorate its film blowing process performance (even unable to blow film), the film quality will also deteriorate, and it is easy to produce crystal points, affecting the appearance of the product. The experimental results also show that compared with Comparative Example 4, the mechanical properties of the enhanced PBAT prepared in Comparative Example 1 are improved, but the melt index of the enhanced PBAT particles is reduced, the torque is also increased, and the processing performance is deteriorated. In Examples 1-4 of the present invention, self-reinforced particles and films are prepared by a two-step method. Compared with Control Example 4, the mechanical properties are significantly improved, the melt index of the self-reinforced PBAT particles obtained is only slightly decreased, and the torque is only slightly increased, indicating that it maintains the good processing properties of the conventional PBAT; Compared with Control Example 1, the mechanical properties of PBAT in Example 3 are further improved. Surprisingly, the processing properties of the self-reinforced PBAT particles obtained by the two-step method are much better than those of the enhanced PBAT particles obtained by the uniform reaction method. When produced using large-scale equipment, the self-reinforced PBAT of the present invention (Example 5) also has good mechanical properties and processing properties, indicating that the method of the present invention is suitable for large-scale production.
[0071] Figure 3The graph shows the changes of complex viscosity and storage modulus of PBAT samples obtained from some embodiments and control examples in a rotational rheometer as a function of angular frequency. Complex viscosity refers to the difficulty of deformation of the material under shear stress, and is related to rheological stress. The greater the rheological stress, the greater the complex viscosity of the polymer material. The storage modulus is the ability to store energy. The larger the storage modulus, the stronger the elastic behavior of the material. However, if it is too high, flow defects will easily occur during the processing: melt fracture and extrusion swell. Therefore, if it is too high, it is not suitable for processing such as film blowing. Figure 3 It can be seen that the PBAT samples prepared in Examples 1-3 of the present invention have higher complex viscosity as the ADR content increases, which is because the branched structure increases the entanglement of macromolecules, thereby increasing the complex viscosity. In addition, the viscosity of the sample obtained in Example 3 is lower than that of the sample in Control Example 1, which may be attributed to the shear and branching reactions that occur simultaneously in the second step of the two-step process, resulting in the formation of a heterogeneous structure. In this structure, highly branched PBAT regions coexist with low-branched or even unbranched PBAT regions, the latter as a continuous phase, giving the composite material a lower complex viscosity to ensure better fluidity, which also shows that the PBAT enhanced by this self-enhancing method is easier to process. Control Example 3 uses peroxide to initiate cross-linking of PBAT, which will significantly increase its complex viscosity and storage modulus, and the melt index will also decrease. This is because the cross-linking network formed by the peroxide initiator and the cross-linking agent is denser and stronger than the branching reaction of ADR, which reduces the molecular chain mobility of PBAT and is not conducive to processing.
[0072] from Figure 4 As can be seen in the embodiment ( Figure 4 (c), (d), (e)) are self-reinforced PBAT prepared by the two-step method. The samples show obvious surface fluctuations, evolving from the initial small protrusions to the subsequent island structure of continuous lamellar structure, while the control example 1 sample ( Figure 4 (b) does not have obvious surface undulations. Figure 4 In the phase distribution observed by AFM of (f), it is obvious that there is a dual continuous phase structure in the sample of Example 3. In general, these observations confirm the presence of a reinforcing phase, which is responsible for enhancing performance, while the pure PBAT continuous phase maintains fluidity and good processing properties in the self-reinforced PBAT.
Claims
1. A method for preparing a self-enhanced PBAT, characterized in that: The preparation method comprises the following steps: (1) Premix conventional PBAT particles, crosslinking agent, lubricant, antioxidant, and anti-blocking agent in a high-speed mixer according to a certain mass ratio, and then extrude and granulate in a twin-screw extruder to obtain reinforced PBAT particles. The processing temperature range of the twin-screw extruder is 80 o C-145 o C, the mass percentages of the components of the PBAT to be enhanced are: PBAT 95.5-99.6%, cross-linking agent 0.2-3.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%; the cross-linking agent is ADR4468; (2) The PBAT particles to be enhanced and the conventional PBAT particles are mixed and mixed in a twin-screw extruder to extrude and granulate to obtain self-enhanced PBAT particles, wherein the mass of the PBAT particles to be enhanced accounts for 10-40% of the total mass of the PBAT particles to be enhanced and the conventional PBAT particles; the processing temperature range of the twin-screw extruder is 80 o C-185 o C.
2. The preparation method according to claim 1, characterized in that: The mass percentages of the components of the PBAT to be enhanced are: PBAT 98.0-99.4%, cross-linking agent 0.25-1.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%.
3. The preparation method according to claim 1, characterized in that: The mass percentages of the components of the PBAT to be enhanced are: PBAT 98.5-99.0%, cross-linking agent 0.5-0.75%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%.
4. The preparation method according to claim 1, characterized in that: In step (1), the lubricant is selected from one or more of PE wax, stearic acid, butyl stearate, stearic acid monoglyceride, and oleamide; the antioxidant is selected from one or more of hindered phenol antioxidants and phosphite antioxidants; and the anti-blocking agent is selected from one or more of pentaerythritol stearate and calcined silica.
5. The preparation method according to claim 1, characterized in that: In step (1), the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-145 o C, die temperature is 110-140 o C, screw speed is controlled at 150-300 rpm; In step (2), the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-185 o C, die temperature is 150-170 o C, the screw speed is controlled at 250-400 rpm.
6. A method for preparing a self-reinforced PBAT film, comprising the following steps: (1) Premix conventional PBAT particles, crosslinking agent, lubricant, antioxidant, and anti-blocking agent in a high-speed mixer according to a certain mass ratio, and then extrude and granulate in a twin-screw extruder to obtain reinforced PBAT particles. The processing temperature range of the twin-screw extruder is 80 o C-145 o C, the mass percentages of the components of the PBAT to be enhanced are: PBAT 95.5-99.6%, cross-linking agent 0.2-3.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%; the cross-linking agent is ADR4468; (2) The PBAT particles to be enhanced and the conventional PBAT particles are mixed and mixed in a twin-screw extruder to extrude and granulate to obtain self-enhanced PBAT particles, wherein the weight of the PBAT particles to be enhanced accounts for 10-40wt% of the total weight of the PBAT particles to be enhanced and the conventional PBAT particles; the processing temperature range of the twin-screw extruder is 80 o C-185 o C; (3) The self-reinforced PBAT particles are blown into a film to obtain a self-reinforced PBAT film.
7. The preparation method according to claim 6, characterized in that: The mass percentages of the components of the PBAT to be enhanced are: PBAT 98.0-99.4%, cross-linking agent 0.25-1.0%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%.
8. The preparation method according to claim 6, characterized in that: The mass percentages of the components of the PBAT to be enhanced are: PBAT 98.5-99.0%, cross-linking agent 0.5-0.75%, lubricant 0.1-0.5%, antioxidant 0.1-0.5%, and anti-blocking agent 0.1-0.5%.
9. The preparation method according to claim 6, characterized in that: In step (1), the lubricant is selected from one or more of PE wax, stearic acid, butyl stearate, stearic acid monoglyceride, and oleamide; the antioxidant is selected from one or more of hindered phenol antioxidants and phosphite antioxidants; and the anti-blocking agent is selected from one or more of pentaerythritol stearate and calcined silica.
10. The preparation method according to claim 6, characterized in that: In step (1), the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-145 o C, die temperature is 110-140 o C, screw speed is controlled at 150-300 rpm; In step (2), the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw diameter is 35-75 mm, the screw aspect ratio is greater than 20:1 but not more than 56:1, and the temperature of the extruder section 1 to 10 is 80-185 o C, die temperature is 150-170 o C, the screw speed is controlled at 250-400 rpm.
Citation Information
Patent Citations
Preparation method of high-starch-content filled PBAT composite film
CN117603481A
Full-biodegradable composite material as well as preparation method and application thereof
CN113583402A
Completely biodegradable film and preparation method thereof
CN113956630A
Epoxy chain extender master batch for PBAT (poly (butylene adipate-co-terephthalate)) film blowing as well as preparation method and application of epoxy chain extender master batch
CN115948033A
Enhanced PBAT and preparation method and application thereof
CN117004004A